The chronicity and timing of prenatal and antenatal maternal depression and anxiety on child outcomes at age 5. Issue 6 (17th May 2020) - Hentges, Rochelle F.; Graham, Susan A.; Fearon, Pasco; Tough, Suzanne; Madigan, Sheri
Abstract: Background: Maternal depression and anxiety have been associated with deleterious child outcomes. It is, however, unclear how the chronicity and timing of maternal mental health problems predict child development outcomes. The aim of the current study was to assess the effect of both chronicity and timing of maternal anxiety and depression in pregnancy, infancy, and the toddler period on children's internalizing and externalizing symptoms, as well as social and communication skills at age 5. Method: Participants were 1, 992 mother–child pairs drawn from a large prospective pregnancy cohort. Mothers reported on anxiety and depression symptoms with clinical screening tools at six time points between <25 weeks gestation and 3 years postpartum. Child outcomes were assessed at age 5. Results: Effect sizes were small for brief incidents of depression/anxiety and increased for intermittent and chronic problems (i.e., three or more timepoints) compared with mothers who had never experienced clinical‐level anxiety or depression. Maternal anxiety/depression during pregnancy, infancy, and toddlerhood predicted all child outcomes, even after controlling for depression/anxiety during the other timepoints. However, maternal anxiety and depression during toddlerhood had a stronger association with child internalizing/externalizing symptoms and communication skills than either prenatal or postpartum depression/anxiety. Conclusions: Increasing number of exposures to clinical‐level anxiety and depression is related to poorer child outcomes. Neither prenatal nor postpartum periods emerged as "sensitive" periods. Rather, maternal depression and anxiety during toddlerhood was more strongly associated with child outcomes at age 5. Results highlight the need for continued support for maternal mental health across early childhood.